Management of the difficult Airway - suodabeh hadadi; atefeh salmani (Journal of Holistic Nursing and Midwifery)
The appropriate airway management is the important point during the anesthesia. For it dose, ‎taking history, physical examination (head and neck, mandible, mouth opening, neck ‎movements …) must be done completely and they are helpful in estimating difficult ‎intubation.‎ It is necessary to note that one case from every ‎‏5000‏‎ cases of anesthesia, not only intubation is ‎not possible but also ventilation is impossible. Direct difficult laryngoscopy happens in ‎‏1.5-‏‏8.5%‏‎ of cases and failed intubation occurs in ‎‏0.13-0.3%‏‎ of cases.‎ Above mentioned points indicated that airway management is important and vital and in the ‎airway difficulties, ventilation auxiliaries such as LMA, combitube, TTJV, and tracheostomy ‎must be used to save patient's life.‎